Arquitetura e percepção bioclimática em habitações ribeirinhas na Amazônia brasileira - Celuppi, Maria Cristina (2018)
The riverside dwellings of Amazonas maintain a direct relationship with nature and are developed from the vernacular architecture, becoming an example of the relation between social, cultural, ecological and economic factors. Inserted in a region of equatorial climate, characterized by high values of temperature and humidity of the air, besides being constantly submitted to the oscillations of the rivers, these dwellings must respond to the natural factors to which they are exposed and to provide thermally comfortable environments to the users. In this way, the objective of this research was to evaluate the thermal comfort in the riverside dwellings of the city of Manacapuru, in the state of Amazonas, in order to confer better conditions of comfort to these environments. To elucidate the objectives, this research had a bibliographical survey throughout the study period; field visits for the collection of meteorological and user perceptual data; models of adaptive thermal comfort and simulations, through numerical modeling to verify the use of bioclimatic strategies. The results pointed to perception and thermal preference in relation to cooler environments, however it was statistically observed that the climatic acceptance of the local inhabitants does not corroborate with the perceptive answers. It was verified that the adaptive comfort model for Southeast Asia is valid and applicable for the region of study and the same indicated, in parallel with the statistics of the questionnaires, that the Brazilian performance standards may be underestimating the adaptability of the residents of that region. The energy simulations presented the thermal scenarios with the use of different coverages for the analyzed dwelling, indicating simple and economically feasible strategies for use in the riverside dwellings of Manacapuru - AM.